2013
DOI: 10.1016/j.surg.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative antibiotics for surgical site infection in pancreaticoduodenectomy: Does the SCIP-approved regimen provide adequate coverage?

Abstract: Introduction-The Joint Commission Surgical Care Improvement Project (SCIP) includes performance measures aimed at reducing surgical site infections (SSI). One measure defines approved perioperative antibiotics for general operative procedures. However, there may be a subset of procedures not adequately covered with the use of approved antibiotics. We hypothesized that piperacillin-tazobactam is a more appropriate perioperative antibiotic for pancreaticoduodenectomy (PD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 23 publications
3
90
0
1
Order By: Relevance
“…Surgical site infections occurred in nine of 44 (20%) patients, which lies within the broad range of incidence reported in the literature of 6–50% . Blood culture and surgical site infection site culture isolates correlated with at least one intraoperative specimen culture isolate in seven of 10 (70%) patients, which is comparable to the correlation rate of 30–59% reported in other studies …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Surgical site infections occurred in nine of 44 (20%) patients, which lies within the broad range of incidence reported in the literature of 6–50% . Blood culture and surgical site infection site culture isolates correlated with at least one intraoperative specimen culture isolate in seven of 10 (70%) patients, which is comparable to the correlation rate of 30–59% reported in other studies …”
Section: Discussionsupporting
confidence: 84%
“…Age, sex, tumour factors, neoadjuvant chemotherapy, preoperative biliary stenting, surgery type, surgeon and perioperative antimicrobial prophylaxis coverage of intraoperative specimen culture isolates were not associated with any statistically significant difference in outcomes. Conversely, several retrospective observational studies have demonstrated that adjustment of perioperative antimicrobial prophylaxis regimens to cover the micro‐organisms isolated from pre‐ and intraoperative and surgical site infection specimen cultures decreases the incidence of surgical site infections . In another retrospective observational study, multivariate analysis demonstrated that intraoperative bile specimen culture isolate resistance to perioperative antimicrobial prophylaxis was the only statistically significant independent risk factor for surgical site infection .…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, most surgeons (57%) prefer the standard agents (cephalosporin with or without metronidazole). However, piperacillin‐tazobactam was shown to be superior in reducing SSI after PD as it covers Enteroccoccus and Enterobacter sp., which are not covered by SCIP‐approved perioperative antibiotics . In this cohort, only 9% of experts use piperacillin‐tazobactam as prophylactic antibiotic.…”
Section: Discussionmentioning
confidence: 98%
“…Surgical site infections following PD vary from 7 to 32% , and contribute to increased length of hospital stay and re‐admissions . The presence of a postoperative SSI increases hospital costs by 32.4% after PD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation